2022
DOI: 10.1177/03635465221078311
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With an Intra-articular Infection After Anterior Cruciate Ligament Reconstruction: A Large Single-Institution Cohort Study

Abstract: Background: An intra-articular infection after anterior cruciate ligament (ACL) reconstruction (ACLR) is a rare complication but one with potentially devastating consequences. The rare nature of this complication raises difficulties in detecting risk factors associated with it and with worse outcomes after one has occurred. Purpose: To (1) evaluate the association between an infection after ACLR and potential risk factors in a large single-center cohort of patients who had undergone ACLR and (2) assess the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 33 publications
0
49
1
Order By: Relevance
“…
A cohort study recently investigated factors associated with intra-articular infection after anterior cruciate ligament reconstruction (ACLR). 2 In this study, which involved 11,451 ACLR procedures, the authors found a higher incidence of infection in revision cases and younger patients. Additionally, bone-patellar tendon-bone autografts were associated with the lowest risk of infection after ACLR as compared with hamstring tendon autografts and allografts.
…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…
A cohort study recently investigated factors associated with intra-articular infection after anterior cruciate ligament reconstruction (ACLR). 2 In this study, which involved 11,451 ACLR procedures, the authors found a higher incidence of infection in revision cases and younger patients. Additionally, bone-patellar tendon-bone autografts were associated with the lowest risk of infection after ACLR as compared with hamstring tendon autografts and allografts.
…”
mentioning
confidence: 69%
“…In addition, we noted that the definition of “younger” in this study 2 is unclear, and it is suggested that a clear definition be provided. Finally, we sincerely thank the authors for their great contribution, which provides significant evidence for further reducing infection after ACLR.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…It is possible to use either an internal or external focus of attention to learn and get better at motor tasks. With an internal focus of attention, the athlete would concentrate on the movements themselves, giving cues to keep their knee correctly positioned over their second toe, for example [38] . The athlete would concentrate on the effect and result of the movement if there was an external focus of attention, such as giving cues to keep their knee in line with a cone or another target.…”
Section: Prevention and Carementioning
confidence: 99%